Optimal Wage Redistribution in the Presence of Adverse Selection in the Labor Market - Spencer Bastani; Tomer Blumkin; Luca Micheletto (Institute for the Study of Labor (IZA), 2015)
In this paper we allude to a novel role played by the non-linear income tax system in the presence of adverse selection in the labor market due to asymmetric information between workers and firms. We show that an appropriate choice of the tax schedule enables the government to affect the wage distribution by controlling the transmission of information in the labor market. This represents an additional channel through which the government can foster the pursuit of its redistributive goals.
Keywords: D82; H21; J31; 330; adverse selection; labor market; optimal taxation; pooling; redistribution